Penetapan Dispensasi Kawin Di Bawah Umur Di Pengadilan Agama Kabupaten Purworejo - Nur Fajar, Bobi Yusuf (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
This research focuses on Marriage Dispensation in the Religious Court of Purworejo, with an emphasis on the factors underlying the granting of marriage dispensation to underage children and the psychological considerations of judges in determining marriage dispensation permits. The result of empirical normative research is elucidating the practice of marriage dispensation, wherein marriages can proceed even if one or both prospective spouses have not reached the minimum age limit as stipulated by Law No. 16 of 2019. Judges grant dispensation based on considerations of expediency, with three reasons: theological motivation to avoid violating religious norms, social motivation to prioritize the long-term interests of the child, and psychological motivation involving the mental preparedness of the husband and wife in dealing with family issues. This research provides insights to marriage institutions and serves as a reference for parties involved in underage marriage cases in society.